Seroprevalence of celiac diseases in children suffering from severe acute malnutrition in age group of 1–5 years - Meena, Pradeep; Meena, Mahendra; Khan, Namir; Meena, Priyanka (Indian Journal of Child Health, 2019)
Introduction: Celiac disease (CD) may be an underlying cause of malnutrition. Aim: The objective of this study was to find out the seroprevalence of CD in children suffering from severe acute malnutrition (SAM) in age group of 1–5 years. Materials and Methods: This was a prospective, observational, hospital-based study carried out at Malnutrition Treatment Centre attached with tertiary care pediatric hospital associated with the medical college of southern Rajasthan, from December 2017 to November 2018. A total of 110 children with SAM were enrolled and screened for CD on the basis of celiac serology (tissuetransglutaminase [tTg]-immunoglobulin A/G [IgA/IgG]). Results: Celiac serology was positivity in 30 (27.28%) cases; out of total 30 seropositive cases, 14 (46.66%) cases were seropositive for both tTg-IgA and IgG, while only tTg-IgA and only tTg-IgG were positive in 9 (30%) and 7 (23.33%) cases, respectively. Mean serotiter of serum tTg-IgA and IgG in seropositive cases was 134.01±198.74 and 49.05±25.74 unit/ml. Conclusions: High seroprevalence of CD in SAM should be taken as alert as CD may be an underlying cause and responsible for malnutrition. These children should be screened by celiac serology (tTg-IgA/IgG) to rule out CD.